Case of successful treatment of a patient with ischemictracheoesophageal and tracheopleural fistulas after a mckeown hybrid esophagectomy - E. A. Kruglov; Yu. A. Pobedinseva; E. V. Filimonov; A. A. Ilin; Yu. A. Kolotilov; I. N. Yablokov; I. V. Chervonogorodskij; V. M. Unguryan (Исследования и практика в медицине, 2020)
The occurrence of tracheal fistulas of ischemic genesis combined with the failure of esophagogastroanastomosis and the communication between them is a rare and formidable complication after esophagectomy with mediastinal lymphadenectomy due to its anatomical position and extensiveness. However, it is insufficiently documented in the literature, both in terms of treatment and in terms of its causes. This observation aims to demonstrate the rare cause of this complication and the atypical successful treatment. In this case, a patient with squamous cell carcinoma G2 of the middle third of the esophagus and TNM stage cT3NxM0. On the McKeown thoracoscopic-laparotomy esophagectomy intraoperatively a short arterial vessel with a diameter of about 3 mm, which passed through the paracancerous infiltration and supplied blood to the esophagus and trachea revealed. The vessel was not isolated from the infiltrate, but was clipped and crossed between the aorta and infiltrate to maintain surgery ablastic. On the 7th day after the operation the insolvency of esophagogastroanastomosis, the fistula of the trachea with mediastinum and the communication between the leak of esophagogastroanastomosis and the fistula of the trachea were diagnosed. We consider this combination as a special case of esophagogastroanastomosis fistula, complicated by the communication between the right pleural cavity and pneumothorax. According to our experience, partial leak of esophagogastroanastomosis successfully heals by secondary tension within 10–15 days against the background of cervicotomic wound drainage and feeding through a nasointestinal tube. In this case there was a leak of saliva in the mediastinum and its penetration into the lumen of the trachea and the right pleural cavity. Surgical diversion of the fistula and stenting of the trachea were considered, but not applied, as the fistula in our opinion was controlled, but the aggressive content of the gastric conduit prevented healing. The patient was on assisted lung ventilation with minimal pressure support and inflow increased oxygen fractio. For this reason, we considered the best stenting of the esophagogastroanastomosis leak area to be covered with a stent in order to stop the aggressive content of the gastric stem from entering the fistula, which led to the successful treatment of the developed severe complication. It should be noted that this method of treatment may be ineffective in patients who need pressure support during ventilation.